Body composition and blood pressure in 6-year-old singletons born after pre-implantation genetic testing for monogenic and structural chromosomal aberrations: a matched cohort study. Issue 4 (1st September 2018) - Belva, F; Roelants, M; Kluijfhout, S; Winter, C; De Schrijver, F; Desmyttere, S; De Rycke, M; Tournaye, H; Liebaers, I; Bonduelle, M
Abstract: STUDY QUESTION: Does Day 3 embryo biopsy for pre-implantation genetic testing for monogenic (PGT-M) and structural chromosomal aberrations (PGT-SR) affect body composition and blood pressure readings of 6-year-old singletons? SUMMARY ANSWER: This study of 87 PGT-M and PGT-SR conceived singletons showed no differences in anthropometric measurements and blood pressure readings in comparison with a matched cohort of peers born after ICSI without embryo biopsy. WHAT IS KNOWN ALREADY: While neonatal outcomes after PGT conception have been found comparable to those after ICSI without embryo biopsy, only a few studies have reported outcomes after PGT at older ages. Moreover, embryo biopsy is also applied in couples who opt for PGT-M and PGT-SR and hence are not necessarily infertile. Health parameters and in particular body composition data in this group of children are lacking. STUDY DESIGN, SIZE, DURATION: This single-centre matched-pair cohort study evaluated body composition of 6-year-old children born after fresh blastocyst embryo transfer with or without embryo biopsy performed at Day 3 for the purpose of PGT-M and PGT-SR. For each child born after embryo biopsy, a singleton born after transfer of a fresh ICSI embryo at the blastocyst stage and reaching the age of 6 years between May 2011 and June 2017 was matched as closely as possible for gender, age, maternal educational level and birth order. PARTICIPANTS/MATERIALS, SETTING, METHODS: Anthropometry (weight, height, BMI, skinfold thickness, waist and mid-upper arm circumference) and blood pressure readings in a longitudinally followed cohort of 87 singletons conceived by PGT-M and PGT-SR and a pairwise matched sample of 87 children conceived by ICSI are described. Results are adjusted for current, neonatal and parental characteristics. MAIN RESULTS AND THE ROLE OF CHANCE: From the 124 eligible PGT-M and PGT-SR families, 110 could be reached of whom 23 refused and 87 (87/110 = 79%) participated. All anthropometric measurements, including z -scores of BMI, waist and mid-upper arm circumference, were comparable between the PGT-M and PGT-SR (−0.23; 0.27; 0.17, respectively) and ICSI (−0.29; 0.11; 0.11, respectively) groups (all P > 0.05). Furthermore, indices of peripheral (triceps) and central (subscapular) adiposity derived from skinfold thickness were comparable (PGT-M and PGT-SR: 14.7 mm; 11.6 mm and ICSI: 15.5 mm; 11.5 mm) as well as the percentage total body fat mass derived from these (PGT-M and PGT-SR: 13.7% and ICSI: 13.9%) (all P > 0.05). Z -scores for blood pressure were also comparable between the PGT and ICSI groups (all P > 0.05). Results did not change when adjusted for neonatal (birthweight, birth order), current (age) and parental (smoking during pregnancy, parental BMI) characteristics. Hospitalization rate and surgical intervention rate were not different for PGT-M and PGT-SR children compared to matched peers born after ICSI. LIMITATIONS, REASONS FOR CAUTION: Although our study describes the largest cohort of singletons born after embryo biopsy worldwide, we were only able to detect moderate differences in anthropometrics and blood pressure with our sample size. WIDER IMPLICATIONS OF THE FINDINGS: Although Day 3 embryo biopsy followed by blastocyst transfer is not associated with adverse outcomes regarding anthropometry and blood pressure, future studies should focus on outcomes in children born after trophectoderm biopsy and/or transfer of warmed embryos after vitrification. STUDY FUNDING/COMPETING INTEREST(s): This study was supported by Methusalem grants and by grants from Wetenschappelijk Fonds Willy Gepts; all issued by the Vrije Universiteit Brussel (VUB). All co-authors, except M.B. declared no conflict of interest. M.B. has received consultancy fees from MSD, Serono Symposia and Merck. The Universitair Ziekenhuis Brussel (UZ Brussel) and the Centre for Medical Genetics have received several educational grants from IBSA, Ferring, Organon, Shering-Plough, Merck for establishing the database for follow-up research and organizing the data collection.